1968
DOI: 10.1021/jo01268a020
|View full text |Cite
|
Sign up to set email alerts
|

Dehydrofluorination of amine metalloid fluorides. II. Reaction of phosphorus pentafluoride with primary amines

Abstract: Phosphorus pentafluoride is shown to react with primary amines to give a variety of products depending upon the amine, solvent, and reaction conditions. An adduct was isolated from aniline, Z,Wimethylaniline, and n-propylamine but could not be isolated from 2,6diethylaniline or isopropylamine under the mildest conditions employed (0-10') in heptane or benzene. Disproportionation of the adduct from aniline and n-propylamine in the presence of phosphorus pentafluoride gave the corresponding amine hexafluorophosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0
2

Year Published

1969
1969
2005
2005

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 0 publications
0
4
0
2
Order By: Relevance
“…The establishment of the adducts was based on infrared spectral data and the stoichiometry of the reaction system. 40 Methylamine reacts to form a 1:2 adduct, PF 5 ‚2MeNH 2 , but upon dissolution, the fine structure in the NMR spectra indicated that the product contained only octahedral phosphorus atoms analogous to the ethylamine and tert-butylamine adducts. 41 Side or further reaction may occur when an excess of amine is used, thus forming the corresponding bis-(alkylamino)trifluorophosphoranes (eq 3).…”
Section: Hexacoordinate Phosphorus (V) a Lewis Acid−base Adductsmentioning
confidence: 99%
See 1 more Smart Citation
“…The establishment of the adducts was based on infrared spectral data and the stoichiometry of the reaction system. 40 Methylamine reacts to form a 1:2 adduct, PF 5 ‚2MeNH 2 , but upon dissolution, the fine structure in the NMR spectra indicated that the product contained only octahedral phosphorus atoms analogous to the ethylamine and tert-butylamine adducts. 41 Side or further reaction may occur when an excess of amine is used, thus forming the corresponding bis-(alkylamino)trifluorophosphoranes (eq 3).…”
Section: Hexacoordinate Phosphorus (V) a Lewis Acid−base Adductsmentioning
confidence: 99%
“…Formation of phosphorus pentafluoride monoalkylamine , and dialkylamine adducts have been reported as have the adducts with other nitrogen heterocycles . The reactions of alkylamines with phosphorus pentafluoride ( 5 ) frequently leads to the formation of more than one product, but the 1:1 adducts can often be separated from other products by sublimation.…”
Section: Hexacoordinate Phosphorus (V)mentioning
confidence: 99%
“…Die mo È glichen Austauschprozesse fu È r einen viergliedrigen Ring mit einem pentavalenten Phosphoratom wurden z. (6)), jedoch deutlich kleiner als in der phenylsubstituierten Verbindung (918.2 Hz) [33]. [38] beschrieben.…”
Section: Darstellung Der Hexafluordiazadiphosphetidineunclassified
“…B. in Lit. Der Wert der n-propylsubstituierten Verbindung (897.2 Hz) [33] stimmt dagegen sehr gut mit dem fu È r 12 bestimmten Wert u È berein. Aus dem Abstand zwischen den Linien mit den gro È ûten Intensita È ten ergibt sich im 19 F-NMR-Spektrum |N|, das sich aus J AX + J AX' zusammensetzt.…”
Section: Darstellung Der Hexafluordiazadiphosphetidineunclassified
“…The quite considerable fluctuations in the yield of the final products are probably associated with the thermal stability of the initial dialkylaminodifluorodihalogenophosphoranes, which increases appreciably on passing from the brominated to the chlorinated products, and reaches a maximum in the fluorophosphoranes (the fluorophosphoranes RJNPFJCIJ, where R = CH 3 , C 2 H 5 , C 4 H 9 , are less stable at corresponding temperatures). * A more detailed investigation of the interaction between phosphorus pentafluoride and primary amines has recently been reported 109 . Compounds RNHPF 4 cannot be isolated or even detected here, cyclic derivatives of the type…”
mentioning
confidence: 99%